2021
DOI: 10.3389/fnmol.2021.756607
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of GlyR α3 Subunits to the Sensitivity and Effect of Ethanol in the Nucleus Accumbens

Abstract: The glycine receptor (GlyR), a ligand-gated ion channel, is critical for inhibitory neurotransmission in brainstem, spinal cord, and in supraspinal regions. Recent data from several laboratories have shown that GlyRs are expressed in the brain reward circuitry and that α1 and α2 are the principal subunits expressed in the nucleus accumbens (nAc). In the present study, we studied the sensitivity to ethanol of homomeric and heteromeric α3 GlyR subunits in HEK293 cells and dissociated neurons from the nAc. Finall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Previous GLRA3 studies have mainly focused on what function the subunit has in the brain, i.e. in the cortex [ 19 ], striatum, nucleus accumbens [ 15 , 19 ], hippocampus [ 19 , 25 , 28 ] and the brainstem [ 17 , 29 ]. For instance, McCracken et al (2017) showed that GLRA3-containing GlyRs are found in various areas of the forebrain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous GLRA3 studies have mainly focused on what function the subunit has in the brain, i.e. in the cortex [ 19 ], striatum, nucleus accumbens [ 15 , 19 ], hippocampus [ 19 , 25 , 28 ] and the brainstem [ 17 , 29 ]. For instance, McCracken et al (2017) showed that GLRA3-containing GlyRs are found in various areas of the forebrain.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that Glra3 participates in tonic inhibition in the prefrontal cortex and in both the dorsal striatum and nucleus accumbens [ 19 ]. San Martin et al (2021) investigated the potential role of the GLRA3 subunit in ethanol sensitivity by focusing on the nucleus accumbens [ 15 ]. They concluded that GLRA3 is expressed in low levels in the mouse nucleus accumbens [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EtOH can pass the blood–brain barrier (BBB) to interact with the CNS and influence the psychological state (Popoola & Cameron, 2018; Schuckit, 2018; Thiele et al, 2000). EtOH can disinhibit dopaminergic neurons by acting on the mesocorticolimbic system including the prefrontal cortex (PFC), ventral tegmental area (VTA), and nucleus accumbens (NAc), while EtOH at a high dose may non‐specifically suppress cortical excitation and cause sedation (Pal et al, 2018; San Martin et al, 2021; Vore et al, 2021). Thus, sensitivity to EtOH is determined by both EtOH metabolism and individual vulnerability of the CNS to EtOH (Aguayo et al, 2014; Chen et al, 2021; Schuckit, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…For example, some missense mutations increase the sensitivity to glycine (α1 I43F ), prolong the decay rate of inhibitory postsynaptic currents (IPSCs; α1 I43F , α1 W170S , α1 Q266E , α1 V280M , α1 R414H ), or induce spontaneous GlyR channel opening (α1 I43F , α1 Y128C , α1 W170S , α1 Q226E , α1 V280M , α1 R414H , β L285R ). GlyRs containing the α3 and α4 subunits have not yet been linked to human disease, but studies using knockout and knockin mice have implicated GlyR α3 in central pain sensitization (Harvey et al, 2004;Werynska et al, 2021), rhythmic breathing (Manzke et al, 2010), and ethanolmediated behaviors (Blednov et al, 2015;San Martin et al, 2021). GlyR α4 is a pseudogene in humans but contributes to touch-evoked escape behaviors in zebrafish (Leacock et al, 2018) and impacts embryonic development and litter sizes in rodents (Nishizono et al, 2020).…”
Section: Introductionmentioning
confidence: 99%